2022
DOI: 10.1038/s41533-022-00300-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of non-steroidal anti-inflammatory drugs (NSAIDs) in COVID-19

Abstract: Early in the COVID-19 pandemic, anecdotal reports emerged suggesting non-steroidal anti-inflammatory drugs (NSAIDs) may increase susceptibility to infection and adversely impact clinical outcomes. This narrative literature review (March 2020–July 2021) attempted to clarify the relationship between NSAID use and COVID-19 outcomes related to disease susceptibility or severity. Twenty-four relevant publications (covering 25 studies) reporting original research data were identified; all were observational cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…In a recent study, the analysis of aspirin users was part of the larger study of smartphone app users from the United States, United Kingdom, and Sweden. The study showed that the probability of developing COVID-19 in this group was not substantially different from those who did not use any NSAIDs (HR after adjustment: 1.03 [95% CI 0.83–1.28]) ( Kushner et al, 2022 ).…”
Section: Nsaids In Covid-19 Managementmentioning
confidence: 96%
“…In a recent study, the analysis of aspirin users was part of the larger study of smartphone app users from the United States, United Kingdom, and Sweden. The study showed that the probability of developing COVID-19 in this group was not substantially different from those who did not use any NSAIDs (HR after adjustment: 1.03 [95% CI 0.83–1.28]) ( Kushner et al, 2022 ).…”
Section: Nsaids In Covid-19 Managementmentioning
confidence: 96%
“…Therapeutics trialed and utilized before and during COVID-19 disease (e.g., methylprednisolone and dexamethasone) naturally can have non-specific anti-inflammatory and specific functions to decrease inflammation in different pathologies affected by multiple cellular pathways [ 226 ]. Therefore, some of the COVID-19-disease-related pathologies, such as lung fibrosis that is associated with alveolar injury, oedema, hypoxia, and inflammation, would, in effect, be reduced while the immune system responds; however, these are subject to local pharmacovigilance and monitoring studies [ 261 , 262 , 263 , 264 ].…”
Section: Inflammatory Cells and Phagocytesmentioning
confidence: 99%
“…Despite initial concern regarding the use of NSAIDs in the setting of a COVID-19 infection, current guidelines per the World Health Organization and Food and Drug Administration have not acknowledged any link between NSAIDs and worsening COVID-19 symptoms or outcomes [39 , 40], and recent studies do not support restricting the use of NSAIDs [41][42][43]. In the absence of robust evidence on the management of COVID-19-associated pericarditis, standard treatments for pericarditis, including NSAIDs, corticosteroids, colchicine, and anakinra, have been used safely in the setting of SARS-COV2 infection [34,44].…”
Section: Pericarditis Due To Covid-19 Infection and Covid-19 Vaccinationmentioning
confidence: 99%